Budaya Organisasi Dan Inovasi Pelayanan: Menyimak Pengalaman Dari Kecamatan Di Lingkungan Pemerintah Kabupaten Agam, Sumatera Barat - Safitri, Yudiantarti (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
An organization’s culture is something that created, transformed, or cared for by members of the organization. Whereas innovation can be explained as a process in which economic and social values are combined to from a science which is developed and implemented in order to increase a product, process, or new service. An innovation to an organization cannot be separated from the organization’s ability to learn. An organization’s culture needs to keep developing in order to create innovation which leads to increased performance in local government. Regency districts have developed many innovations to public service. The public service innovation that has been developed is a perfect collaboration between local governments (that tried to develop organizational cultures) and local citizens (who honor the local culture.) Positive combinations of organizational cultures and local cultures are able to create a public service innovation for sub district in Agam regency governmental area